Accounting students’ approaches to learning in University of Waikato, New Zealand / Nur Fakhzan Marwan - Marwan, Nur Fakhzan (2004)
There are concerns over the quality of students’ learning given that insufficiencies of current accounting education programmes and structure conduct to unseemly preparation for future accountants to live their professional life. Critics argue that today's accountants need a broad-based education that will enable them to think more critically and analytically. However it is important for educators to understand first how students learn. The purpose of this study is to investigate accounting students’ approaches to learning in University of Waikato, New Zealand. There are two approaches to learning: surface and deep. A survey questionnaire was constructed and distributed randomly to the first, second, third, fourth and fifth financial accounting stream students. From the results of the survey, it is found that majority students tend to adopt a surface approach. However, the use of surface approach declines after their first year of study, while the deep approach employed increases slowly throughout the years. In terms of gender differences, males are found to favour deep approach, while females tend to adopt surface approach in their learning. For age category, younger students (below 22 years old) prefer to adopt surface approach, while older students (between 23-40 years old) are indifferent in their approaches to learning. The findings suggest that age, maturity and experiences have no significant relationships with the approach to learning. In ethnic groups, European students tend to adopt surface approach, while Asian students are found to use deep approach in their learning. These results demonstrate that the cultural differences may have some impacts how students learning